The religious element in the interpretation of the events of ‘Persian War’ - Baptista, Lyvia Vasconcelos (Romanitas - Revista de Estudos Grecolatinos, 2015)
Procopius of Caesarea, a Byzantine historian, in the sixth century AD, provided very different pictures of the Justinian´s ruler. The author, in his Works, also provided a heterogeneous set of religious information that still leads many historians to discuss the meaning of his beliefs and importance of Divine Providence in the interpretation of events. The purpose of this article is to emphasize the religious element in the Persian War, discussing the use of Christian references, in a fatalistic way, in order to criticizing the Emperor Justinian. Also we will discuss the role of God and Tykhe in the explanation of events.